The Relationship Between Pre-service Teachers' Spatial Experience and Spatial Visualisation at a Rural-based University. Issue 1 (2nd January 2021) - Kok, Petrus Jacobus
Abstract : Over several years, first-year pre-service education students regularly experienced difficulty with engineering graphics activities. Research has already established that these activities require the use of well-developed spatial visualisation which is, for the most part, determined by a persons' spatial experience. The importance of this study was that very little is known about rural students' spatial experience; therefore, this quantitative study focused on the relationship between students' pre-university spatial life experience and spatial visualisation at a South African university in KwaZulu–Natal province. Fifty females and 50 males were randomly selected from a cohort of first-year engineering graphics students. The study was grounded in the socio-cultural learning theory which advances that learning is both a physical and an intellectual activity. Therefore, the assumption was that the nature and repetition of spatial-type life experience have had an impact on the acquisition and retention of spatial visualisation. Following a non-experimental design, two research instruments, a Spatial Experience Questionnaire and a Spatial Visualisation Test, were used to quantify a Spatial Experience score and a Spatial Visualisation score, respectively. Correlation and linear regression were used to investigate the significance of the relationship. Overall, spatial life experience did not have any significant correlation with students' spatial visualisation; however, within the constructs of spatial activities, playing traditional games and using computers were significant predictors. In contrast to previous studies, sketching was not sufficient evidence to predict spatial visualisation. The study recommends that teachers in spatial visualisation-dependent subjects, such as technology and engineering graphics design, could include games with a strong eye–hand–foot coordination component as well as playing and doing computer-type activities to enhance learners' spatial visualisation.